Predictive Factors for the Success of Vaginal Dinoprostone for the Induction of Labour - Liu W; Guo L; Feng L; Wang J; Zhang M; Fan X (Dove Medical Press, 2024)
Wenjie Liu, Li Guo, Lizhen Feng, Jie Wang, Miao Zhang, Xiaobin Fan Department of Obstetrics and Gynecology, Xi'an No.3 Hospital, The Affiliated Hospital of Northwest University, Xi'an, 710018, People's Republic of ChinaCorrespondence: Xiaobin Fan, Email liuwj0709@163.comObjective: To evaluate factors predictive of the success of a slow-release dinoprostone vaginal insert for cervical ripening.Methods: This retrospective study included 187 women who received dinoprostone vaginal inserts for cervical ripening. The participants were divided into two groups: the transvaginal delivery group (n = 87) and cesarean section termination group (n = 100). The correlation between the parameters present before cervical ripening with dinoprostone slow release and its success, as well as complications and adverse outcomes, was analyzed. Cesarean section predictors and area under the curve (AUC) were compared between the two Groups.Results: There were statistical differences between the two groups in body mass index (BMI), height, cervical Bishop score, cephalic position, time of medication use, and fetal head position at the time of medication use (P< 0.05). The optimal thresholds for identifying cesarean section in dinoprostone vaginal insert for cervical ripening were 162.5 for height (AUC = 0.61), 10.65 cm for amniotic fluid index (AUC = 0.6), S-2.5 for cephalic position (AUC = 0.61), 5.5 for bishop score of cervix (AUC = 0.65). The height, amniotic fluid index, cephalic position, and Bishop score of the cervix were included in the same model. The AUC value of the combined model was higher than the AUC value of the single factor.Conclusion: The combined model was a better predictor of cesarean section in dinoprostone vaginal inserts for cervical ripening and labor induction. The success of cervical ripening with a dinoprostone slow-release vaginal insert can be predicted by the factors that can be recognized at admission.Keywords: dinoprostone, cervical ripening, labor induction, predictive model